Keberlanjutan bentuk fisik arsitektur Huta Siallagan Samosir dalam mendukung wisata budaya Geopark Kaldera Toba - Rumiati Rosaline Tobing; Andi Kumala Sakti; Hanny (ARTEKS : Jurnal Teknik Arsitektur, 2020)
Toba Lake is one of Indonesia's most priority destinations included in the UNESCO Global Geopark. This makes it increasingly famous, necessitating its continued maintenance and preservation. Tourism is one of the economic sources of revenue in Indonesia. Since 2019, the government is determined to increase revenue from the tourism sector, with a target of 20 million tourists. The development of priority destinations influences environmental and socio-cultural maintenance and provides economic opportunities to local tourism village communities. The Huta Siallagan area of Samosir Regency is a village known for the beginning of the law enforcement civilization in Samosir. This tourist village has a stone trials site aged about 500 years, as one of the cultural attractions. The Stone Trial has been maintained for hundreds of years, becoming an interest to tourists, and one of the historical sites included in the Toba Caldera Geopark's geo- site. As a result, its sustainability needs to be maintained. The Samosir Regency Government is implementing the sustainability of tourism. This study showed a a survival aspect from an architectural viewpoint, reflected in the form of Huta Siallagan. The study aimed to determine the survival value in Huta Siallagan. A case study was used to explore architecture, tradition and life due to society's cultural aspects.